How economics explains the world : a short history of humanity - Leigh, Andrew, 1972- (Mariner Books, 2024)
Economist Andrew Leigh presents a dramatically new understanding of human history. Spanning ancient times to the current day, he reveals the hidden economic factors that have shaped every aspect of our world, from determining the outcomes of wars to the endurance of social transformations.